2012
DOI: 10.1666/10068.1
|View full text |Cite
|
Sign up to set email alerts
|

Climatic forcing of Quaternary deep-sea benthic communities in the North Pacific Ocean

Abstract: There is growing evidence that changes in deep-sea benthic ecosystems are modulated by climate changes, but most evidence to date comes from the North Atlantic Ocean. Here we analyze new ostracod and published foraminiferal records for the last 250,000 years on Shatsky Rise in the North Pacific Ocean. Using linear models, we evaluate statistically the ability of environmental drivers (temperature, productivity, and seasonality of productivity) to predict changes in faunal diversity, abundance, and composition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 95 publications
4
44
0
Order By: Relevance
“…The Ostracoda fossil record is of greatest value for tracing palaeo-climate events, providing valuable information on past water salinity, temperature and chemistry, hydrodynamic conditions, substrate characteristics, climate, sea level variations, oxygen and nutrient availability (Frenzel and Boomer 2005) and anthropogenic influences (Irizuki et al 2015). Yasuhara et al (2012aYasuhara et al ( , 2014 used ostracod and foraminiferal fossil records from the last 250,000 years on the Shatsky Rise in the North Pacific Ocean to demonstrate that rapid climate changes affect deep-sea benthic diversity. They observed glacial-interglacial shifts in overall abundances and species diversities for both meiofauna taxa.…”
Section: Meiofaunal Organisms As Useful Test Case Of Climate Change Smentioning
confidence: 99%
“…The Ostracoda fossil record is of greatest value for tracing palaeo-climate events, providing valuable information on past water salinity, temperature and chemistry, hydrodynamic conditions, substrate characteristics, climate, sea level variations, oxygen and nutrient availability (Frenzel and Boomer 2005) and anthropogenic influences (Irizuki et al 2015). Yasuhara et al (2012aYasuhara et al ( , 2014 used ostracod and foraminiferal fossil records from the last 250,000 years on the Shatsky Rise in the North Pacific Ocean to demonstrate that rapid climate changes affect deep-sea benthic diversity. They observed glacial-interglacial shifts in overall abundances and species diversities for both meiofauna taxa.…”
Section: Meiofaunal Organisms As Useful Test Case Of Climate Change Smentioning
confidence: 99%
“…Indeed, environmental (temperature and POC flux) impacts on deep-sea species diversity and microfossil accumulation rate (here we used this as a proxy for biomass, i.e. ecosystem functioning) are well described [36,62,65,67,69]. Microfossil accumulation rate is a proxy for POC flux [47,69] and here we used it as a proxy for ecosystem function.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…ecosystem functioning) are well described [36,62,65,67,69]. Microfossil accumulation rate is a proxy for POC flux [47,69] and here we used it as a proxy for ecosystem function. Manipulative BEF experiments usually look into biodiversity effects on ecosystem function, whereas this palaeoobservational study investigated correlations between these effects, which are usually interpreted as POC-flux impact on biodiversity.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…Although too numerous to review, benthic foraminiferal assemblages have been shown to be linked to surface ocean productivity (Gooday, 1988) and the benthic foraminiferal accumulation rate (BFAR) index has been used as a tool to investigate glacial-interglacial changes in ocean productivity (Herguera and Berger, 1991;Herguera, 2000) (see Gooday, 2003;Jorissen et al, 2007 for reviews). Ostracode species diversity is also correlated to POC variability over orbital timescales (Yasuhara et al, 2012).…”
Section: Microfossil Density As a Paleoceanographic Proxymentioning
confidence: 99%